Industry 4.0 and the small business : something behind the technology – a literature review - Dias Lopes, José (Serbian Journal of Management, 2022)
Small and medium-sized enterprises (SMEs) are especially vulnerable to technology issues, often because they lack the financial resources or the skills to properly exploit new technologies.This paper presents the results of a study that explores the link between Industry 4.0 and SMEs through a systematic literature review. The results show that this link is dominated by themes that can be grouped into the following categories: "Industrial revolutions", "Technology", "Management", "Operations Management/ Industrial Engineering", "Social issues/ Sustainability", and “Methodology”. The study shows the relevance of the topics Management, Social Issues, and Sustainability, which is not then reflected in publications of articles on Industry 4.0 in journals in these areas. Eventually, the establishment of partnerships between research teams in these areas of knowledge and the teams studying Industry 4.0 could mitigate this insufficiency. The themes Social Issues and Sustainability are underrepresented and therefore an effort is needed to develop research on the impacts of these themes on Industry 4.0 and vice versa.